1957
DOI: 10.1152/ajplegacy.1957.191.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Metabolism in Dairy Cows

Abstract: Metabolism of C14 fructose has been studied in dairy cows and the results compared to those obtained earlier with C14 glucose. C14 fructose disappeared rapidly from the plasma; simultaneously there occurred an immediate rise in plasma glucose C14. The pattern of isotope distribution in milk C and the peak expired CO2 specific activity was the same after fructose as after glucose injection. These results suggest that glucose is a key intermediate in the metabolism of fructose—the conversion of fructose to gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1962
1962
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…This is primarily because it has long been believed that fructose is rapidly metabolised to glucose in ruminants and that this glucose may then modulate insulin release (Luick et al 1957). The results of experiment 1, while supporting these earlier data in terms of the conversion of fructose to glucose, show that the insulin response to fructose challenge is much more prolonged than that induced by glucose and suggest a more complicated relationship.…”
Section: Methodssupporting
confidence: 66%
See 2 more Smart Citations
“…This is primarily because it has long been believed that fructose is rapidly metabolised to glucose in ruminants and that this glucose may then modulate insulin release (Luick et al 1957). The results of experiment 1, while supporting these earlier data in terms of the conversion of fructose to glucose, show that the insulin response to fructose challenge is much more prolonged than that induced by glucose and suggest a more complicated relationship.…”
Section: Methodssupporting
confidence: 66%
“…The results of experiment 1, which involved a standard 'glucose tolerance test', in which a large bolus of glucose was injected directly into the peripheral circulation demonstrated the classic acute insulin response and rapid clearance of glucose from the blood observed in most species (Bloomfield et al 2007). A similar challenge with galactose, however, resulted in a smaller but more prolonged increase in insulin and slow clearance from the peripheral circulation whereas a fructose bolus, despite being apparently rapidly converted to glucose (Luick et al 1957), resulted in a much more prolonged period of insulin release. Thus, it appears that the control of insulin release is far more complex than indicated by the responses obtained to a standard glucose challenge and this suggestion is supported by the results obtained in experiment 2 following the systemic infusion of much lower doses of monosaccharide; doses that were designed not to perturb peripheral insulin concentrations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although we found that granulosa cells cultured in the presence of fructose were able to respond to insulin in a dose-dependent manner, the fact that SLC2A4 mRNA expression responded differentially to identical doses of glucose and fructose suggests that SLC2A4 was not acting as a major fructose transporter in sheep granulosa cells. In the ruminant, dietary fructose is thought to be rapidly metabolised to glucose in the liver (Luick et al 1957, Boda 1964, but in sheep, we have observed insulin responses to a fructose challenge which differ in terms of duration and magnitude to identical doses of glucose (Onions et al 2009), and both direct ovarian and systemic infusions of fructose had stimulatory effects on ovarian androstenedione and E 2 secretion (Onions et al 2009). The current study supports these in vivo findings and shows that fructose may have a direct effect on ovarian function, but more work is required to clarify the physiological basis and mechanism of these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, there is currently little evidence for a direct effect of fructose on the ovary. In one study, SLC2A5 mRNA expression was not detected in the rat ovary (Kol et al 1997), and in the ruminant, fructose is thought to be rapidly metabolised to glucose in the liver (Luick et al 1957) which may then trigger insulin release. In the primate and the human, fructose has little effect on insulin and leptin release or on the concentrations of blood glucose (Curry 1989, Havel 1997, Teff et al 2004, but in sheep, we have observed increased insulin secretion in response to a challenge with fructose that differs in terms of duration and magnitude to challenges with identical doses of glucose (Onions et al 2009).…”
Section: Introductionmentioning
confidence: 99%